The Effect of Paracetamol Inhibitor Concentration and Immersion Time to The Corrosion Rate and Toughness in 3% NaCl Media - Ulum, Miftachul; Rosidah, Afira Ainur (Universitas Mercu Buana, 2024)
Corrosion is one of the main problems causing damage to metals. The occurrence of a reaction with the surrounding environment accompanied by several factors cause deterioration so that corrosion causes damage to the material. Therefore, researchers added inhibitors as a way to control corrosion. This study used paracetamol as an inhibitor against corrosion protection of AISI 1020 steel with 3% NaCl as the media. The method used for the corrosion test was the weight loss and toughness test using the Charpy method of impact testing. This study obtained the lowest corrosion rate value at the addition of 220 ppm inhibitor concentration with immersion time for 7 days of 1.078 mpy. The efficiency observed in this study showed that adding an inhibitor concentration of 220 ppm with the immersion time of 7 days had the highest value reaching 71.42%. Moreover, the impact test results got the highest value on the 220 ppm inhibitor variation with the immersion time of 7 days, reaching 0.0817 J/